NATIONAL HEALTH COVERAGE SYSTEM : PHARMACISTS AND JKN PARTICIPANT SATISFACTION IN PRIMARY HEALTH FACILITIES - Satibi Satibi (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2016)
National Health Insurance is a health protection system for participants to obtain health care benefits and protection to meet basic health needs that organized based on social insurance and equity principles. JKN in cooperation with the primary health facilities to provide comprehensive health services including pharmacy services. Pharmacist responsible for drug availability and affordability that affected by drug procurement process, drug distribution process, and drug cost claiming process.This research’s aim to determine relationship between national health insurances services to pharmacists satisfaction and to determine relationship between pharmacy services to outpatient satisfaction at primary health facilities. Data used in research are primary data that collected through questionnare and interview. The method used is purposive sampling which the data is analyzed using linear and multiple regresion and see significant value (p). The number of respondents was 40 pharmacists and 150 patients in health centers and primary clinics scattered in Sleman, Bantul, and Kota Yogyakarta. The results showed that the process of procurement and distribution of drugs have a relationship with a pharmacist satisfaction while drug costs not process claims with consecutive p 0.010, 0.002, and 0.261. Related to the satisfaction of the outpatient pharmacy services result there is a relationship of drug availability (p = 0.003), service time (p = 0.006), and get drug (p = 0.000) to the satisfaction of outpatients. The conclusion of this study is the process of procurement and distribution of drugs have a relationship with a pharmacist satisfaction. In addition, the availability of pharmacy services such as medication, a drug services, and the provision of drug information also has a significant relationship to the satisfaction of outpatients in health facilities first rate.Keywords: pharmacy services, pharmacists, patients, JKN